Home electrical power control and monitoring system based on the Internet of Things (IoT) - Aditya, Handre; Elvanny Myori, Dwiprima (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The increasing demand for electrical energy in Indonesia is often not balanced with efficiency of use, especially in the household sector. Energy waste due to lack of real-time monitoring and control of electricity consumption is a serious problem. To address this problem, an Internet of Things (IoT)-based home electrical power control and monitoring system has been designed and built. This research aims to develop a prototype system that is able to monitor and control the use of electrical power remotely through applications on smartphones. The system uses an ESP32 microcontroller as the main processing unit, a PZEM-004T sensor to measure electrical parameters such as voltage (Volts), current (Ampere), power (Watts), and energy (kWh), and a relay module to control the flow of electricity to electronic devices. The measurement data is displayed in real-time on the TFT touchscreen LCD screen and the Blynk app on the smartphone, which also serves as a control interface.. With the implementation of this system, it is hoped that it can increase public awareness of the more efficient use of electrical energy and provide solutions in saving electrical energy.